Variação geográfica em Sporophila (Aves: thraupidae) com base em evidências fenotípicas, ecológicas e genéticas - Repenning, Márcio (2017)
This work reveals the diversity of cryptic forms within the most emblematic birds from the Neotropical grasslands, the Seedeaters, Sporophila, a group with rapid diversification rate with evidence of ongoing speciation. The background question of the study is how this biological diversity is generated and maintained in this genus of birds, which are characterized by the great capacity of dispersion and low susceptibility to geographic isolation by physic brakes. Using multiple analytical tools, morphological, vocalization, biogeographic and molecular characteristics were studied to explain the extent of intra and interspecific variations and how lineages can be formed. As study model, two Sporophila superspecies with wide and concordant geographic distribution inner South America were sampled throughout of whole range, the Plumbeous Seedeater and Capuchinos. The results show marked dichotomy between the more general patterns of radiation or divergence of the lineages in each of the groups. Plumbeous Seedeeater represent a small cluster of incipient species with adaptive radiation, whereas the radiation in Capuchinos does not involve morphological adaptations. Lineages of Capuchinos diverge in allopatric/peripatric from their breeding populations and changes in vocalizations without the formation of local dialects covariate to changes in the color of the breeding plumage of males. In both groups, it was possible to detect a cryptic diagnosable diversity beyond the traditionally current known species. Divergent or differentiated lineages ongoing were corroborated by neutral genetic signals at different sorting levels. Contact of these lineages/taxa was simulated experimentally to test their skill to discriminate heterospecific closely related species provide assortative mate predisposition. The results are confronted with the knowledge about the mechanisms of speciation in birds in a natural and sexual selection scenario among populations that may have diversified after geographic isolation or via ecological speciation. Finally, a taxonomic classification useful to represent the biological diversification in the studied Sporophila is suggested.